Pendekatan Desain Berpusat pada Manusia untuk Pengembangan Aplikasi Penjualan Kredit Produk Kedirgantaraan: Evaluasi System Usability Scale - Alis Susilawati; Erwin Teguh Arujisaputra; Adam Husain; Sri Erina Damayanti (JESII: Journal of Elektronik Sistem InformasI, 2026)
PT. SAS Aero Sishan faces challenges in monitoring production data and managing credit sales information efficiently, resulting in delayed decision-making processes. This study aims to design an aerospace product credit sales application using the Human-Centered Design (HCD) approach and evaluate its usability using the System Usability Scale (SUS). The research was conducted through four HCD stages: requirement gathering, analysis, prototype development, and evaluation. Data were collected through observation, interviews, documentation, and usability testing involving 30 respondents. The usability evaluation produced an average SUS score of 72.42, with descriptive statistics indicating a median score of 70, a minimum score of 50, a maximum score of 100, and a standard deviation of 13.14. The obtained SUS score falls into Grade B (Good), indicating that the proposed application provides acceptable usability and effectively supports users in managing credit sales activities. The findings demonstrate that applying the Human-Centered Design approach successfully accommodates user requirements and improves user satisfaction. This study contributes a user-centered framework for developing credit sales information systems in the aerospace industry and provides a practical reference for future usability-oriented system development.